2003
DOI: 10.1046/j.1365-4362.2003.01951.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trichloroacetic acid solution and cryosurgery in the treatment of solar lentigines

Abstract: Cryosurgery was found to be superior to TCA 30% solution in the treatment of solar lentigines. This study demonstrates that old-fashioned treatments for solar lentigines are still excellent and cost-effective therapeutic choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…The principles underlying this treatment are that glycolic acid decreases the incidence of postinflammatory pigment changes, whereas TCA is able to penetrate deeply but uniformly into the skin. 24 The efficacy of chemical peels has been compared with that of cryotherapy 25 and laser therapy. 14 The first comparative study involved treating each hand of 25 patients with multiple solar lentigines at random with either 30% TCA or liquid nitrogen spray as a single treatment.…”
Section: Chemical Peelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles underlying this treatment are that glycolic acid decreases the incidence of postinflammatory pigment changes, whereas TCA is able to penetrate deeply but uniformly into the skin. 24 The efficacy of chemical peels has been compared with that of cryotherapy 25 and laser therapy. 14 The first comparative study involved treating each hand of 25 patients with multiple solar lentigines at random with either 30% TCA or liquid nitrogen spray as a single treatment.…”
Section: Chemical Peelsmentioning
confidence: 99%
“…14 The first comparative study involved treating each hand of 25 patients with multiple solar lentigines at random with either 30% TCA or liquid nitrogen spray as a single treatment. 25 Patients were evaluated at 8 weeks using photography. At this time, 9 patients (47%) in the TCA group achieved more than 50% improvement compared with 15 patients (71%) in the cryotherapy group; the difference was significant (P \.05).…”
Section: Chemical Peelsmentioning
confidence: 99%
“…Similar findings were reported by Golforoushan et al () showing that cryotherapy was more effective in the opinion of 56.7% of patients. Other studies also demonstrated that cryotherapy was considered better by 62–68% of the patients (Goldust et al, ; Lugo‐Janer et al, ; Raziee et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Chemical peels with 30–35% trichloroacetic acid solution or brief (i.e., <10 s) cryotherapy with liquid nitrogen have resulted in significant lightening of SL, but data are limited on long‐term improvements, and recurrences are common. Additionally, cryotherapy can be painful, and prolonged treatment is associated with hypopigmentation 9–11 . Laser therapy for SL has shown benefit in at least one small, randomized controlled trial, with effectiveness superior to liquid nitrogen cryotherapy, but postinflammatory hyperpigmentation is a known complication 11–13 …”
Section: Discussionmentioning
confidence: 99%